A Data Repository System for the Information Technology Department using Google Site - Concepcion, Alaina Thea V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The study describes the development of the data repository system for Bulacan State University’s Department of Information Technology that was accomplished using Google Sites. The system is an orderly, accessible mechanism for storage, conservation, and administration of digital resources. Quantitative research was conducted to utilize questionnaires and document analysis to investigate whether there is a need for a central repository. The respondents were randomly chosen using simple random sampling, and they comprised domain experts and department members who were lecturers. The repository was analyzed using the ISO 25010:2011 method to optimize the appreciable challenges presented in document fixing, including duplicating files and links, the lack of ample space, data corruption, the inadequacy of keywords in the search, and the issue of migration. Using Google Sites to implement it, thus making the system more accessible and usable thus this can be a practical example of a departmental document repository. It supports its purpose in improving productivity, accessibility, and long-term preservation. The study demonstrates that the use of the developed system largely reduces errors associated with document management and presents an organized, efficacious, and dependable central mechanism in addressing the common challenges in digital resource conservation and retrieval.